PERMISSIBILITY OF APPEAL FOR REVIEW OF JUDICIAL DECISION RENDERED ADMINISTRATIVE COURT IN CONDITIONS OF REGULAR ADMINISTRATIVE LEGAL PROTECTION - Миленковић, Невена (COLLECTION OF PAPERS, FACULTY OF LAW NIŠ, 2022)
The succession of administrative and administrative court protection, their intertwining and multiple connection is reflected in the conditionality of the possibility of providing one (and only in domestic law devolutive) type of extraordinary administrative court protection by the existence and previous exhaustion of regular administrative legal protection. Starting from the thesis on the integrity of administrative and administrative court protection, the author discusses how the existence, i.e. the position of court practice on the (non) existence of means of regular administrative protection affects the party’s ability to protect itself through the Appeal ensuing from the Article 49 of the Law on Administrative Disputes (LAD) as an instrument of extraordinary administrative court protection. As one of the three types of situations provided by the Law on Administrative Disputes in which it is possible to file an Appeal for an extraordinary review of the court decision rendered by the Administrative Court, the LAD envisages "things in which an appeal was excluded in the administrative procedure". As the current Law on Administrative Procedure envisages (in addition to an appeal) an objection as a means of regular legal protection, the question of its legal relevance to the admissibility of the use of the Appeal for Extraordinary Review of a Court Decision arises. Can the existence of an objection be considered a regular legal remedy in administrative proceedings? An affirmative answer, consequently, would lead to the conclusion of rejecting the Appeal under LAD and denying protection under it. A negative answer would provide the Appeal with wider application in practice. In practical terms, the position on this issue has a far broader scope and significance. Depending on the way of approaching the presented issues, taking one or another presented position is significantly unequally reflected on the forthcoming reform of the system of secondary administrative protection in terms of the need to introduce another (appellate) instance.